2007
DOI: 10.1063/1.2803764
|View full text |Cite
|
Sign up to set email alerts
|

Microwave absorption properties and mechanism of cagelike ZnO∕SiO2 nanocomposites

Abstract: In this paper, cagelike ZnO∕SiO2 nanocomposites were prepared and their microwave absorption properties were investigated in detail. Dielectric constants and losses of the pure cagelike ZnO nanostructures were measured in a frequency range of 8.2–12.4GHz. The measured results indicate that the cagelike ZnO nanostructures are low-loss material for microwave absorption in X band. However, the cagelike ZnO∕SiO2 nanocomposites exhibit a relatively strong attenuation to microwave in X band. Such strong absorption i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
128
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 248 publications
(132 citation statements)
references
References 29 publications
2
128
2
Order By: Relevance
“…According to transmission line theory, the RL coefficient (in dB) of the electromagnetic wave (normal incidence) at the surface of a single-layer material backed by a perfect conductor at a given frequency and layer thickness can be defined by Equations (1) and (2): [22] Z…”
Section: Wave-absorption Propertiesmentioning
confidence: 99%
“…According to transmission line theory, the RL coefficient (in dB) of the electromagnetic wave (normal incidence) at the surface of a single-layer material backed by a perfect conductor at a given frequency and layer thickness can be defined by Equations (1) and (2): [22] Z…”
Section: Wave-absorption Propertiesmentioning
confidence: 99%
“…The absence of catalysts and additives is considered as a further advantage of the process since the final products were free of residues from them that may affect the results of characterization. Based on our previous work [8,16,[25][26][27][28][29] , we have designed a new apparatus to prepare ZnO nanostructures with different morphologies. Their optical properties and growth mechanism of the ZnO nanostructures were studied.…”
mentioning
confidence: 99%
“…ZnO was randomly dispersed in the wax matrix, which could not connect with each other in the composites. Therefore, the incontinuous local microcurrent network in the composites was formed [14]. Each porous hollow ZnO will generate strong conductive loss, which leads to the attenuation of microwave energy.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that microwave absorption was affected by the electric resistivity, the aspect ratio and the contents of the whiskers [13]. Cao et al found that cage-like ZnO nanostructures exhibit relative strong microwave absorption in the X band, compared with ZnO nanoparticles [14]. The microwave absorption properties of the ZnO nanowirepolyester composites were also reported [15].…”
Section: Introductionmentioning
confidence: 92%